2015
DOI: 10.1017/s0031182015000475
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis in dogs: is high seroprevalence indicative of a reservoir role?

Abstract: SUMMARYAmerican cutaneous leishmaniasis (ACL) is a complex disease with a rich diversity of animal host species. This diversity imposes a challenge, since understanding ACL transmission requires the adequate identification of reservoir hosts, those species able to be a source of additional infections. In this study we present results from an ACL cross-sectional serological survey of 51 dogs (Canis familiaris), where we used diagnostic tests that measure dog's exposure to Leishmania spp. parasites. We did our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 85 publications
(173 reference statements)
3
27
0
1
Order By: Relevance
“…This possibility is re-enforced by the similar pattern observed for the prevalence of sand fly bite exposure, which indicates endemic transmission, showing higher prevalence in young children and low prevalence in old adults (Anderson and May, 1991;Calzada et al 2015), with a flat prevalence for age groups corresponding to the economically active population, which has a high proportion of migrants in our study area (Confalonieri et al 2014).…”
Section: Distribution Of Anti-lu Longipalpis Saliva Antibody Titressupporting
confidence: 74%
“…This possibility is re-enforced by the similar pattern observed for the prevalence of sand fly bite exposure, which indicates endemic transmission, showing higher prevalence in young children and low prevalence in old adults (Anderson and May, 1991;Calzada et al 2015), with a flat prevalence for age groups corresponding to the economically active population, which has a high proportion of migrants in our study area (Confalonieri et al 2014).…”
Section: Distribution Of Anti-lu Longipalpis Saliva Antibody Titressupporting
confidence: 74%
“…8 To further contextualize our parasite infection and blood meal results, during the study period we found domestic dogs to be present in almost all houses and to have seroprevalence patterns indicative of endemic transmission 15 at TM. Nevertheless, we were unable to detect or isolate parasites from dogs, 15 which does not allow us to implicate this species as a Leishmania spp. reservoir in the studied area.…”
Section: Discussionmentioning
confidence: 89%
“…to humans in Panamá. This species is strongly associated with humans and domestic animals, for example, dogs, 15 infected by (or exposed to) ACL parasites, and its abundance was associated with transmission to humans at the household level. 25 Our results also highlight the importance of implementing active surveillance looking at both anthropophilic and zoophilic species, to better understand the eco-epidemiology of ACL parasite transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study detected IgG antibodies against L. panamensis by IFAT however all blood samples were PCR negative for Leishmania spp. DNA (Calzada et al, 2015).…”
Section: Discussionmentioning
confidence: 99%